Use of nonsteroidal anti-inflammatory drugs and risk of fractures. - van Staa, T; Leufkens, H; Cooper, C (2000)
In animal models, prostaglandin synthesis has been found to mediate bone metabolism. Nonsteroidal anti-inflammatory drugs (NSAIDs), given their inhibitory effects of prostaglandin synthesis, may play a role in the prevention of osteoporosis. The primary objective of this study is to describe and quantify the fracture risks of patients exposed to NSAIDs in a representative general medical practice setting. A retrospective cohort study was conducted in a general medical practice setting in the UK (using data from the General Practice Research Database). Regular NSAID users (who received three or more NSAID prescriptions), aged 18 years or older, were compared with matched control patients and incidental NSAID users. The study comprised 214,577 regular NSAID users, 286,850 incidental NSAID users, and 214,577 control patients. The relative rate of nonvertebral fractures during regular NSAID treatment compared with control was 1.47 (95% confidence interval [CI] 1.42-1. 52) and that of hip fracture 1.08 (0.98-1.19). No differences in nonvertebral fractures were found between the regular and incidental NSAID users (RR = 1.04; 95% CI 0.99-1.09). The rate of nonvertebral fractures among users of diclofenac (RR = 1.00; 95% CI 0.93-1.08) and naproxen (RR = 0.91; 95% CI 0.82-1.00) was similar to that of ibuprofen. The results of this study are not supportive of clinically significant effects of NSAIDs on bone metabolism.